Relationship between public investment, private investment and real income with economic growth in Malaysia, 1996-2006 / Nurul Huda Mohamed Ali - Mohamed Ali, Nurul Huda (2007)
This study is about the relationship of public investment, private investment and real income with economic growth in Malaysia, 1996 - 2006. The main idea for this study is to analyze the performance of public investment, private investment and real income on economic growth in a developing country, Malaysia. Besides that, this study also wants to examine the impact of public investment, private investment and real income towards the growth. The study is using the annual data from 1996 to 2006. The data collection will employs from the DataStream, Economic Report and Bank Negara Malaysia' s annual report. The method use to analyze the relationship of each variable is by Pearson Correlation, Multiple and Single Regression method. The variable involves in this study are real gross domestic product, real income per capita, public investment ratio, and private investment ratio. The result shows that public investment has no relationship towards the growth that measure by GDP. It is because the variable used (public investment ratio) is not a significant contributor to GDP. On the other hand, private investment and real income has a relationship and gives a better performance towards the economy growth in Malaysia.